Designing room temperature sodium sulfur batteries with long cycle-life at pouch cell level - Pampel, Jonas; Doerfler, Susanne; Althues, Holger; Kaskel, Stefan (Energy Storage Materials, 2019)
The successful transfer of room temperature sodium sulfur (RT-Na-S) technology from coin cell to pouch cell level is demonstrated. The general cell design is based on a previously developed RT-Na-S concept implementing hard carbon based anodes. Scalable technologies known from lithium ion battery production are utilized for electrode production. The electrolyte composition, the voltage window as well as the balancing is evaluated on coin cell level leading to optimized parameters. For scaled electrodes and electrolytes, a specific capacity of 418 mAh gS −1 coupled with a high coulombic efficiency of 95.3% can be still obtained in RT-Na-S coin cells after a total of 549 cycles. Residual carbonates in the HC-anode were found to deteriorate the cycling performance. An increased cut-off voltage (1.5 V) significantly raises the coulombic efficiency. Finally, the design is successfully transferred to a 10-layered pouch cell leading to a high energy efficiency of 88.6% and a capacity of 387 mAh gS −1 after a total of 937 cycles. Hence, the present work shows the principle feasibility of a stationary energy storage technology based on RT-Na-S pouch cell technology.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Hard carbon anode; Pouch cell; Sodium sulfur battery; Stationary energy storage